Cytotoxic effects of extract of Acmella oleraceae (Jambú) in Rhipicephalus microplus females ticks - de Oliveira, Patrícia Rosa; de Carvalho Castro, Karina Neoob; Anholeto, Luis Adriano; Camargo Mathias, Maria Izabel (Wiley, 2016)
The present study analyzed the effects of different concentrations of the hexane extract of A. oleraceae (HEAO) (Jambú) on the germ cells of semi-engorged Rhipicephalus microplus female ticks, through a morpho-histological study, evaluating the effectiveness of the extract in the genesis of the individuals. To perform this analysis, 100 semi-engorged females were divided into five groups with 20 individuals each: groups I and II, respectively constituted by distilled water control and 50% ethanol + 1% DMSO, and groups III, IV, and V constituted by treatment with HEAO in the concentrations of 12.5, 25.0 and 50.0 mg/mL, respectively. All the ticks were immersed in the different concentrations of the extract or in distilled water for 5 minutes, dried and conditioned in BOD incubator for 7 days. The individuals of the treatment groups revealed the action of this extract showing alterations in the germ cells of the females from the different groups when compared with those from the groups I and II (control groups). These alterations were mainly related to the size and shape of the oocytes; number of yolk granules; presence, number, size and location of vacuoles in the cytoplasm of all the germ cells; and the presence of nuclear alterations in these cells as well. Thus, it was demonstrated that the concentrations of HEAO affected the germ cells of R. microplus ticks. The effects of the extract are similar to those caused by renowned and efficient chemical products used to control these ticks. Microsc. Res. Tech. 79:744-753, 2016. © 2016 Wiley Periodicals, Inc.
Keywords: cattle; control; cytotoxicity; extract; natural product; tick